This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
n = 0 ∑ 2 0 1 6 ⌊ n 9 + 1 n ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) ( n + 5 ) ⌋ = n = 0 ∑ 3 ⌊ n 9 + 1 n ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) ( n + 5 ) ⌋ = 0 + ⌊ 2 6 ! ⌋ + ⌊ 5 1 3 7 ! ⌋ + ⌊ 2 ⋅ 1 9 6 8 4 8 ! ⌋ = 0 + 3 6 0 + 9 + 1 = 3 7 0 Note.- Let p : N → R such that p ( n ) = n 9 + 1 n ( n + 1 ) ( n + 2 ) ( n + 3 ) ( n + 4 ) ( n + 5 ) , ∀ n ∈ N . Dividing numerator and denominator by n 6 , ∀ n ≥ 1 we'll get p ( n ) = n 3 + 1 / n 6 1 ( 1 + 1 / n ) ( 1 + 2 / n ) ( 1 + 3 / n ) ( 1 + 4 / n ) ( 1 + 5 / n ) the numerator of p ( n ) is a strictly decreasing function ∀ n ≥ 4 and the denominator of p ( n ) is a strictly increasing function ∀ n ≥ 4 and this implies that the function p ( n ) is a strictly decreasing function ∀ n ≥ 4 and p ( 4 ) < 4 3 2 ⋅ 2 ⋅ 2 ⋅ 2 ⋅ ( 2 + 1 / 4 ) = 6 4 3 6 < 1 ...